Solutionbank: Edexcel AS and A Level Modular Mathematics
Solutionbank: Edexcel AS and A Level Modular Mathematics
Solutionbank: Edexcel AS and A Level Modular Mathematics
Solutionbank
Edexcel AS and A Level Modular Mathematics
Partial fractions
Exercise A, Question 1
Question:
Solution:
1 1 4 3 7
3 + 4 = 12 + 12 = 12
Solutionbank
Edexcel AS and A Level Modular Mathematics
Partial fractions
Exercise A, Question 2
Question:
Solution:
3 2 15 8 7
4 5 = 20 20 = 20
Solutionbank
Edexcel AS and A Level Modular Mathematics
Partial fractions
Exercise A, Question 3
Question:
Solution:
3 2
x x+1
3(x+1) 2x
= x(x+1) x(x+1)
3 ( x + 1 ) 2x
= x(x+1)
3x + 3 2x
= x(x+1)
x+3
= x(x+1)
Solutionbank
Edexcel AS and A Level Modular Mathematics
Partial fractions
Exercise A, Question 4
Question:
Solution:
2 3
(x1) + (x+2)
2(x+2) 3(x1)
= (x1) (x+2) + (x1) (x+2)
2(x+2) +3(x1)
= (x1) (x+2)
2x + 4 + 3x 3
= (x1) (x+2)
5x + 1
= (x1) (x+2)
Solutionbank
Edexcel AS and A Level Modular Mathematics
Partial fractions
Exercise A, Question 5
Question:
Solution:
4 2
( 2x + 1 ) + (x1)
4(x1) 2 ( 2x + 1 )
= ( 2x + 1 ) ( x 1 ) + ( 2x + 1 ) ( x 1 )
4 ( x 1 ) + 2 ( 2x + 1 )
= ( 2x + 1 ) ( x 1 )
4x 4 + 4x + 2
= ( 2x + 1 ) ( x 1 )
8x 2
= ( 2x + 1 ) ( x 1 )
Solutionbank
Edexcel AS and A Level Modular Mathematics
Partial fractions
Exercise A, Question 6
Question:
Solution:
7 2
(x3) (x+4)
7(x+4) 2(x3)
= (x3) (x+4) (x3) (x+4)
7(x+4) 2(x3)
= (x3) (x+4)
7x + 28 2x + 6
= (x3) (x+4)
5x + 34
= (x3) (x+4)
Solutionbank
Edexcel AS and A Level Modular Mathematics
Partial fractions
Exercise A, Question 7
Question:
Solution:
3 6
2x (x1)
3(x1) 6 2x
= 2x ( x 1 ) 2x ( x 1 )
3 ( x 1 ) 12x
= 2x ( x 1 )
3x 3 12x
= 2x ( x 1 )
9x 3
= 2x ( x 1 )
9x + 3
or 2x ( x 1 )
3 ( 3x + 1 )
or 2x ( x 1 )
Solutionbank
Edexcel AS and A Level Modular Mathematics
Partial fractions
Exercise A, Question 8
Question:
Solution:
3 2 1
x + (x+1) + (x+2)
3(x+1) (x+2) 2x ( x + 2 ) 1x ( x + 1 )
= x(x+1) (x+2) + x(x+1) (x+2) + x(x+1) (x+2)
3 ( x + 1 ) ( x + 2 ) + 2x ( x + 2 ) + 1x ( x + 1 )
= x(x+1) (x+2) Add numerators
3 ( x2 + 3x + 2 ) + 2x2 + 4x + x2 + x
= x(x+1) (x+2) Expand brackets
3x2 + 9x + 6 + 2x2 + 4x + x2 + x
= x(x+1) (x+2) Simplify terms
6x2 + 14x + 6
= x(x+1) (x+2) Add like terms
Solutionbank
Edexcel AS and A Level Modular Mathematics
Partial fractions
Exercise A, Question 9
Question:
Solution:
4 2 1
3x (x2) + ( 2x + 1 )
4 ( x 2 ) ( 2x + 1 ) 2 3x ( 2x + 1 ) 3x ( x 2 )
= 3x ( x 2 ) ( 2x + 1 ) 3x ( x 2 ) ( 2x + 1 ) + 3x ( x 2 ) ( 2x + 1 )
4 ( x 2 ) ( 2x + 1 ) 2 3x ( 2x + 1 ) + 3x ( x 2 )
= 3x ( x 2 ) ( 2x + 1 ) Add numerators
4 ( 2x2 3x 2 ) 6x ( 2x + 1 ) + 3x2 6x
= 3x ( x 2 ) ( 2x + 1 ) Expand brackets
1x2 24x 8
= 3x ( x 2 ) ( 2x + 1 ) Add like terms
x2 + 24x + 8
or 3x ( x 2 ) ( 2x + 1 )
Solutionbank
Edexcel AS and A Level Modular Mathematics
Partial fractions
Exercise A, Question 10
Question:
Solution:
3 2 4
(x1) + (x+1) + (x3)
3(x+1) (x3) 2(x1) (x3) 4(x1) (x+1)
= (x1) (x+1) (x3) + (x1) (x+1) (x3) + (x1) (x+1) (x3)
3(x+1) (x3) +2(x1) (x3) +4(x1) (x+1)
= (x1) (x+1) (x3) Add numerators
3 ( x2 2x 3 ) + 2 ( x2 4x + 3 ) + 4 ( x2 1 )
= (x1) (x+1) (x3) Expand brackets
9x2 14x 7
= (x1) (x+1) (x3) Add like terms
Solutionbank
Edexcel AS and A Level Modular Mathematics
Partial fractions
Exercise B, Question 1
Question:
2x + 11
(b) (x+1) (x+4)
7x 12
(c) 2x ( x 4 )
2x 13
(d) ( 2x + 1 ) ( x 3 )
6x + 6
(e)
x2 9
7 3x
(f)
x2 3x 4
8x
(g)
x2 + 4x
2x 14
(h)
x2 + 2x 15
Solution:
6x 2 A B
(a) Let (x2) (x+3) (x2) + (x+3) Add the fractions
6x 2 A(x+3) +B(x2)
(x2) (x+3) (x2) (x+3)
So 6x 2 A ( x + 3 ) + B ( x 2 ) Set numerators equal
Substitute x = 2 6 2 2 = A ( 2 + 3 ) + B ( 2 2 )
10 = 5A
A=2
Substitute x = 3 6 ( 3) 2=A( 3+3) +B
( 32)
20 = B 5
B=4
6x 2 2 4
Hence (x2) (x+3) (x2) + (x+3)
2x + 11 A B
(b) Let (x+1) (x+4) (x+1) + (x+4) Add the fractions
2x + 11 A(x+4) +B(x+1)
(x+1) (x+4) (x+1) (x+4)
So 2x + 11 A ( x + 4 ) + B ( x + 1 ) Set numerators equal
Substitute x = 4 2 ( 4 ) + 11 = A ( 4 + 4 ) + B
( 4+1)
3 = 3B
B= 1
Substitute x = 1 2 1 + 11 = A ( 1 + 4 ) + B ( 1 + 1 )
9 = 3A
A=3
2x + 11 3 ( 1) 3 1
Hence (x+1) (x+4) (x+1) + (x+4) (x+1) (x+4)
7x 12 A B
(c) Let 2x ( x 4 ) 2x + (x4) Add the fractions
7x 12 A ( x 4 ) + B 2x
2x ( x 4 ) 2x ( x 4 )
So 7x 12 A ( x 4 ) + 2Bx Set numerators equal
Substitute x = 4 7 4 12 = A ( 4 4 ) + 2B 4
40 = 8B
B= 5
Substitute x = 0 7 0 12 = A ( 0 4 ) + 2B 0
12 = 4A
A=3
7x 12 3 5 3 5
Hence 2x ( x 4 ) 2x + (x4) 2x (x4)
2x 13 A B
(d) Let ( 2x + 1 ) ( x 3 ) ( 2x + 1 ) + (x3) Add the fractions
2x 13 A ( x 3 ) + B ( 2x + 1 )
( 2x + 1 ) ( x 3 ) ( 2x + 1 ) ( x 3 )
So 2x 13 A ( x 3 ) + B ( 2x + 1 ) Set numerators equal
Substitute x = 3 2 3 13 = A ( 3 3 ) + B ( 2 3 + 1 )
7=B7
B= 1
1 1 1
Substitute x = 2 2 2 13 = A 2 3 + B
1
2 2 +1
1
14 = A 3 2
A=4
2x 13 4 1 4 1
Hence ( 2x + 1 ) ( x 3 ) ( 2x + 1 ) + (x3) ( 2x + 1 ) (x3)
6x + 6 6x + 6
(e) (x+3) (x3) Factorise denominator
x2 + 9
6x + 6 A B
Let (x+3) (x3) (x+3) + (x3) Add fractions
6x + 6 A(x3) +B(x+3)
(x+3) (x3) (x+3) (x3)
So 6x + 6 A ( x 3 ) + B ( x + 3 ) Set numerators equal
Substitute x = 3 6 3 + 6 = A ( 3 3 ) + B ( 3 + 3 )
24 = B 6
B=4
Substitute x = 3 6 ( 3) +6=A( 33) +B
( 3+3)
12 = A 6
A=2
6x + 6 2 4
Hence (x+3) + (x3)
x2 9
7 3x 7 3x
(f) (x4) (x+1) Factorise denominator
x2 3x 4
7 3x A B
Let (x4) (x+1) (x4) + (x+1) Add fractions
7 3x A(x+1) +B(x4)
(x4) (x+1) (x4) (x+1)
So 7 3x A ( x + 1 ) + B ( x 4 ) Set numerators equal
Substitute x = 1 7 3 ( 1 ) = A ( 1 + 1 ) + B
( 14)
10 = B 5
B= 2
Substitute x = 4 734=A(4+1) +B(44)
5=A5
A= 1
7 3x 1 2 1 2
Hence (x4) + (x+1) (x4) (x+1)
x2 3x 4
8x 8x
(g) x(x+4) Factorise denominator
x2 + 4x
8x A B
Let x ( x + 4 ) x + (x+4) Add fractions
8x A ( x + 4 ) + Bx
x(x+4) x(x+4)
So 8 x A ( x + 4 ) + Bx Set numerators equal
Substitute x = 0 8 0 = A ( 0 + 4 ) + B 0
8 = 4A
A=2 Substitute x = 4 8 4 =A 4+4
+B 4
12 = 4B
B= 3
8x 2 3 2 3
Hence x + (x+4) x (x+4)
x2 + 4x
2x 14 2x 14
(h) (x+5) (x3) Factorise denominator
x2 + 2x 15
2x 14 A B
Let (x+5) (x3) (x+5) + (x3) Add fractions
2x 14 A(x3) +B(x+5)
(x+5) (x3) (x+5) (x3)
So 2x 14 A ( x 3 ) + B ( x + 5 ) Set numerators equal
Substitute x = 3 2 3 14 = A ( 3 3 ) + B ( 3 + 5 )
8=B8
B= 1
Substitute x = 5 2 ( 5 ) 14 = A ( 5 3 ) + B
( 5+5)
24 = A ( 8 )
A=3
2x 14 3 1 3 1
Hence (x+5) + (x3) (x+5) (x3)
x2 + 2x 15
Solutionbank
Edexcel AS and A Level Modular Mathematics
Partial fractions
Exercise B, Question 2
Question:
2x 5 A B
Show that (4+x) (2x)
can be written in the form (4+x)
+ (2x)
where A
and B are constants to be found.
Solution:
2x 5 A B A(2x) +B(4+x)
Let (4+x) (2x) (4+x) + (2x) (4+x) (2x)
So 2x 5 A ( 2 x ) + B ( 4 + x )
Substitute x = 2 2 2 5 = A ( 2 2 ) + B ( 4 + 2 )
9=B6
3
B= 2
Substitute x = 4 2 4 5=A 2 4 +B
4+ 4
3=A6
1
2 =A
2x 5 A B 1 3
Hence (4+x) (2x) (4+x) + (2x) when A= 2 and B= 2 .
2x 5 1 3
or (4+x) (2x) = 2(4+x) 2(2x)
Solutionbank
Edexcel AS and A Level Modular Mathematics
Partial fractions
Exercise C, Question 1
Question:
2x2 12x 26
(a) (x+1) (x2) (x+5)
10x2 8x + 2
(b) x ( 2x + 1 ) ( 3x 2 )
5x2 19x 32
(c) (x+1) (x+2) (x5)
Solution:
2x2 12x 26 A B C
(a) Let (x+1) (x2) (x+5) (x+1) + (x2) + (x+5) Add
fractions
2x2 12x 26
(x+1) (x2) (x+5)
A(x2) (x+5) +B(x+1) (x+5) +C(x+1) (x2)
(x+1) (x2) (x+5)
So 2x2 12x 26 A ( x 2 ) ( x + 5 ) + B ( x + 1 ) ( x + 5 ) + C
(x+1) (x2)
Substitute x = 2 8 24 26 = A 0 + B 3 7 + C 0
42 = 21B
B= 2
Substitute x = 1 2 + 12 26 = A ( 3 ) 4 + B 0 + C 0
12 = 12A
A=1
Substitute x = 5 50 + 60 26 = A 0 + B 0 + C 28
84 = 28C
C=3
2x2 12x 26 1 2 3
Hence (x+1) (x2) (x+5) (x+1) (x2) + (x+5)
10x2 8x + 2 A B C
(b) Let x ( 2x + 1 ) ( 3x 2 ) x + ( 2x + 1 ) + ( 3x 2 ) Add fractions
10x2 8x + 2 A ( 2x + 1 ) ( 3x 2 ) + Bx ( 3x 2 ) + Cx ( 2x + 1 )
x ( 2x + 1 ) ( 3x 2 ) x ( 2x + 1 ) ( 3x 2 )
So 10x2 8x + 2 A ( 2x + 1 ) ( 3x 2 ) + Bx ( 3x 2 ) + Cx
( 2x + 1 )
Substitute x = 0 0 0 + 2 = A 1 ( 2 ) + B 0 + C 0
2 = 2A
A= 1
1 10 1
Substitute x = 2 4 +4+2=A0+B 2
7
2 +C0
7 7
2 =B 4
B=2
Equate coefficients in x2: 10 = 6A + 3B + 2C
10 = 6 + 6 + 2C
10 = 2C
5=C
10x2 8x + 2 1 2 5
Hence x ( 2x + 1 ) ( 3x 2 ) x + ( 2x + 1 ) ( 3x 2 )
5x2 19x 32 A B C
(c) Let (x+1) (x+2) (x5) (x+1) + (x+2) + (x5)
5x2 19x 32
(x+1) (x+2) (x5)
A(x+2) (x5) +B(x+1) (x5) +C(x+1) (x+2)
(x+1) (x+2) (x5)
So 5x2 19x 32 A ( x + 2 ) ( x 5 ) + B ( x + 1 ) ( x 5 ) + C
(x+1) (x+2)
Substitute x = 1 5 + 19 32 = A 1 ( 6 )
+B0+C0
18 = 6A
A=3
Substitute x = 5 125 95 32 = A 0 + B 0 + C 6 7
252 = 42C
C= 6
Substitute x = 2 20 + 38 32 = A 0 + B 1
7 +C0
14 = 7B
B= 2
5x2 19x 32 3 2 6
Hence (x+1) (x+2) (x5) (x+1) (x+2) (x5)
Solutionbank
Edexcel AS and A Level Modular Mathematics
Partial fractions
Exercise C, Question 2
Question:
6x2 + 7x 3
(a)
x3 x
5x2 + 15x + 8
(b)
x3 + 3x2 + 2x
5x2 15x 8
(c)
x3 4x2 + x + 6
Solution:
(a) x3 x x ( x2 1 ) x ( x + 1 ) ( x 1 )
6x2 + 7x 3 6x2 + 7x 3 A B C
So + +
x3 x x(x+1) (x1) x (x+1) (x1)
A ( x + 1 ) ( x 1 ) + Bx ( x 1 ) + Cx ( x + 1 )
x(x+1) (x1)
Setting numerators equal gives 6x2 + 7x 3 A x+1 x1 + Bx x1
+ Cx x+1
Substitute x = 0 0+03=A1 ( 1) +B0+C0
3 = 1A
A=3
Substitute x = 1 6+73=A0+B0+C12
10 = 2C
C=5
Substitute x = 1 673=A0+B ( 1) ( 2) +C0
4 = 2B
B= 2
6x2 + 7x 3 3 2 5
Hence +
x3 x x (x+1) (x1)
(b) x3 + 3x2 + 2x x ( x2 + 3x + 2 ) x ( x + 1 ) ( x + 2 )
5x2 + 15x + 8 5x2 + 15x + 8 A B C
So + +
x3 + 3x2 + 2x x(x+1) (x+2) x (x+1) (x+2)
A ( x + 1 ) ( x + 2 ) + Bx ( x + 2 ) + Cx ( x + 1 )
x(x+1) (x+2)
Setting numerators equal gives 5x2 + 15x + 8 A x+1 x+2 + Bx x+2
+ Cx x+1
Substitute x = 0 0+0+8=A12+B0+C0
8 = 2A
A=4
Substitute x = 1 5 15 + 8 = A 0 + B ( 1 ) 1 + C 0
2 = 1B
B=2
Substitute x = 2 20 30 + 8 = A 0 + B 0 + C 2 1
2 = 2C
C= 1
5x2 + 15x + 8 4 2 1
Hence +
x3 + 3x2 + 2x x (x+1) (x+2)
5x2 15x 8 A x2 x3 +B x+1 x3 +C x+1
x2
Substitute x = 2 20 30 8 = A 0 + B 3 ( 1 ) + C 0
18 = 3B
B=6
Substitute x = 1 5 + 15 8 = A ( 3 ) ( 4 ) + B 0 + C 0
12 = 12A
A=1
Substitute x = 3 45 45 8 = A 0 + B 0 + C 4 1
8 = 4C
C= 2
5x2 15x 8 1 6 2
Hence +
x3 4x2 +x+6 (x+1) (x2) (x3)
Solutionbank
Edexcel AS and A Level Modular Mathematics
Partial fractions
Exercise D, Question 1
Question:
3x2 + x + 2
x2 ( x + 1 )
Solution:
3x2 + x + 2 A B C
Let + +
x2 (x+1) x x2 (x+1)
Ax ( x + 1 ) + B ( x + 1 ) + Cx2
x2 ( x + 1 )
Solutionbank
Edexcel AS and A Level Modular Mathematics
Partial fractions
Exercise D, Question 2
Question:
x2 10x 5
(x+1) 2(x1)
Solution:
x2 10x 5 A B C
Let 2
(x+1)
+ 2 + (x1)
(x+1) (x1) (x+1)
Solutionbank
Edexcel AS and A Level Modular Mathematics
Partial fractions
Exercise D, Question 3
Question:
2x2 + 2x 18
x(x3) 2
Solution:
2x2 + 2x 18 A B C
Let + +
x(x3) 2 x (x3) (x3) 2
A ( x 3 ) 2 + Bx ( x 3 ) + Cx
x(x3) 2
Solutionbank
Edexcel AS and A Level Modular Mathematics
Partial fractions
Exercise D, Question 4
Question:
7x2 42x + 64
x(x4) 2
Solution:
7x2 42x + 64 A B C
Let + +
x(x4) 2 x (x4) (x4) 2
A ( x 4 ) 2 + Bx ( x 4 ) + Cx
x(x4) 2
Solutionbank
Edexcel AS and A Level Modular Mathematics
Partial fractions
Exercise D, Question 5
Question:
5x2 2x 1
x3 x2
Solution:
x3 x2 x2 ( x 1 )
5x2 2x 1 5x2 2x 1 A B C
So + +
x3 x2 x2 (x1) x x2 (x1)
Ax ( x 1 ) + B ( x 1 ) + Cx2
x2 ( x 1 )
Solutionbank
Edexcel AS and A Level Modular Mathematics
Partial fractions
Exercise D, Question 6
Question:
2x2 + 2x 18
x3 6x2 + 9x
Solution:
x3 6x2 + 9x x ( x2 6x + 9 ) x ( x 3 ) 2
2x2 + 2x 18 2x2 + 2x 18 A B C
So + +
x3 6x2 + 9x x(x3) 2 x (x3) (x3) 2
A ( x 3 ) 2 + Bx ( x 3 ) + Cx
x(x3) 2
Solutionbank
Edexcel AS and A Level Modular Mathematics
Partial fractions
Exercise D, Question 7
Question:
2x
(x+2) 2
Solution:
2x A B A(x+2) +B
Let 2
(x+2) + 2
(x+2) (x+2) (x+2) 2
Set the numerators equal: 2x = A ( x + 2 ) + B
Substitute x = 2 4 = A 0 + B B = 4
Equate coefficients in x: 2=A
2x 2 4
Hence (x+2)
(x+2) 2 (x+2) 2
Solutionbank
Edexcel AS and A Level Modular Mathematics
Partial fractions
Exercise D, Question 8
Question:
x2 + 5x + 7
(x+2) 3
Solution:
x2 + 5x + 7 A B C
Let + 2 +
(x+2) 3 (x+2) (x+2) (x+2) 3
A(x+2) 2+B(x+2) +C
(x+2) 3
Solutionbank
Edexcel AS and A Level Modular Mathematics
Partial fractions
Exercise E, Question 1
Question:
x2 + 3x 2
(a) (x+1) (x3)
x2 10
(b) (x2) (x+1)
x3 x2 x 3
(c) x(x1)
2x2 1
(d)
(x+1) 2
Solution:
x2 + 3x 2 x2 + 3x 2
(a)
(x+1) (x3) x2 2x 3
Divide the numerator by the denominator:
x2 + 3x 2 5x + 1
Therefore (x+1) (x3) 1+ (x+1) (x3)
5x + 1 A B
Let (x+1) (x3) (x+1) + (x3) Add fractions
A(x3) +B(x+1)
(x+1) (x3)
Set the numerators equal: 5x + 1 A ( x 3 ) + B ( x + 1 )
Substitute x = 3 5 3 + 1 = A 0 + B 4
16 = 4B
B=4
Substitute x = 1 5 ( 1) +1=A ( 4) +B0
4 = 4A
A=1
Hence
x2 + 3x 2 5x + 1 1 4
(x+1) (x3) 1+ (x+1) (x3) 1+ (x+1) + (x3)
x2 10 x2 10 x2 + 0x 10
(b)
(x2) (x+1) x2 x 2 x2 x 2
Divide the numerator by the denominator:
x2 10 x8
Therefore (x2) (x+1) 1+ (x2) (x+1)
x8 A B
Let (x2) (x+1) (x2) + (x+1) Add fractions
A(x+1) +B(x2)
(x2) (x+1)
Set the numerators equal: x8A(x+1) +B(x2)
Substitute x = 2 2 8 = A 3 + B 0
6 = 3A
A= 2
Substitute x = 1 18=A0+B ( 3)
9 = 3B
B=3
Hence
x2 10 x8 2 3
(x2) (x+1) 1+ (x2) (x+1) 1+ (x2) + (x+1)
2 3
1 (x2) + (x+1)
x3 x2 x 3 x3 x2 x 3
(c)
x(x1) x2 x
Divide the numerator by the denominator:
x3 x2 x 3 x3
Therefore x(x1) x+ x(x1)
x3 A B
Let x(x1) x + (x1) Add fractions
A ( x 1 ) + Bx
x(x1)
Set the numerators equal: x 3 A ( x 1 ) + Bx
Substitute x = 1 1 3 = A 0 + B 1
4 = 1B
B= 4
Substitute x = 0 3=A ( 1) +B0
A=3
x3 x2 x 3 x3 3 4
Hence x(x1) x+ x(x1) x+ x (x1)
2x2 1 4x 3
Therefore 2 2+
(x+1) (x+1) 2
4x 3 A B
Let 2
(x+1) + Add fractions
(x+1) (x+1) 2
A(x+1) +B
(x+1) 2
Set the numerators equal: 4x 3 A ( x + 1 ) + B
Substitute x = 1 4 ( 1 ) 3 = A 0 + B
1=B
B=1
Equate coefficients in x: 4=A
A= 4
2x2 1 4x 3 4 1
Hence 2 2+ 2 (x+1) +
(x+1) (x+1) 2 (x+1) 2
Solutionbank
Edexcel AS and A Level Modular Mathematics
Partial fractions
Exercise E, Question 2
Question:
4x2 + 17x 11
(a)
x2 + 3x 4
Solution:
4x2 + 17x 11 5x + 5
Therefore 4+ Factorise denominator
x2 + 3x 4 x2 + 3x 4
5x + 5
4+ (x+4) (x1)
5x + 5 A B
Let (x+4) (x1) (x+4) + (x1) Add fractions
A(x1) +B(x+4)
(x+4) (x1)
Set the numerators equal: 5x + 5 A ( x 1 ) + B ( x + 4 )
Substitute x = 1 5 1 + 5 = A 0 + B 5
10 = 5B
B=2
Substitute x = 4 5 ( 4) +5=A ( 5) +B0
15 = 5A
A=3
Hence
4x2 + 17x 11 5x + 5 3 2
4+ 4+ +
x2 + 3x 4 (x+4) (x1) (x+4) (x1)
5x2 17x + 12
x+ Take out a factor of x in the denominator
x3 4x2 + 4x
5x2 17x + 12
x+ Factorise the denominator fully
x ( x2 4x + 4 )
5x2 17x + 12
x+
x(x2) 2
5x2 17x + 12 A B C
Let 2 x + (x2) + Add fractions
x(x2) (x2) 2
A ( x 2 ) 2 + Bx ( x 2 ) + Cx
x(x2) 2
Solutionbank
Edexcel AS and A Level Modular Mathematics
Partial fractions
Exercise E, Question 3
Question:
Solution:
5 1
3x + 2 + (x1) + (x+3)
So A = 2, B = 3, C = 5 and D = 1
Pearson Education Ltd 2009
Solutionbank
Edexcel AS and A Level Modular Mathematics
Partial fractions
Exercise F, Question 1
Question:
7x2 + 2x 2
(b)
x2 ( x + 1 )
15x + 21
(c) (x2) (x+1) (x5)
x2 + 1
(d) x(x2)
Solution:
x3 A B
(a) Let x(x1) x + (x1) Add the fractions
A ( x 1 ) + Bx
x(x1)
Set the numerators equal: x 3 A ( x 1 ) + Bx
Substitute x = 1 1 3 = A 0 + B 1
B= 2
Substitute x = 0 03=A ( 1) +B0
3 = 1A
A=3
x3 3 2
Hence x(x1) x (x1)
7x2 + 2x 2 A B C
(b) Let + + Add the fractions
x2 ( x + 1 ) x x2 (x+1)
Ax ( x + 1 ) + B ( x + 1 ) + Cx2
x2 ( x + 1 )
Set the numerators equal:
7x2 + 2x 2 Ax ( x + 1 ) + B ( x + 1 ) + Cx2
Substitute x = 0 0 + 0 2 = A 0 + B 1 + C 0
2 = 1B
B= 2
Substitute x = 1 722=A0+B0+C1
3 = 1C
C=3
Equate coefficients in x2: 7=A+C Substitute C = 3
7=A+3
A=4
7x2 + 2x 2 4 2 3
Hence +
x2 ( x + 1 ) x x2 (x+1)
15x + 21 A B C
(c) Let (x2) (x+1) (x5) (x2) + (x+1) + (x5) Add the fractions
A(x+1) (x5) +B(x2) (x5) +C(x2) (x+1)
(x2) (x+1) (x5)
Set the numerators equal:
15x + 21 A ( x + 1 ) ( x 5 ) + B ( x 2 ) ( x 5 ) + C ( x 2 ) ( x + 1 )
Substitute x = 1 15 + 21 = A 0 + B ( 3 ) ( 6 ) + C 0
36 = 18B
B=2
Substitute x = 5 75 + 21 = A 0 + B 0 + C 3 6
54 = 18C
C= 3
Substitute x = 2 30 + 21 = A 3 ( 3 ) + B 0 + C 0
9 = 9A
A=1
15x + 21 1 2 3
Hence (x2) (x+1) (x5) (x2) + (x+1) (x5)
x2 + 1 x2 + 1 x2 + 0x + 1
(d)
x(x2) x2 2x x2 2x + 0
Divide the numerator by the denominator:
x2 + 1 2x + 1
Therefore x(x2) 1+ x(x2)
2x + 1 A B A ( x 2 ) + Bx
Let x(x2) x + (x2) x(x2)
Set the numerators equal: 2x + 1 A ( x 2 ) + Bx
Substitute x = 0 1 = A ( 2 ) + B 0
1 = 2A
1
A= 2
Substitute x = 2 22+1=A0+B2
5 = 2B
5
B= 2
Hence
1 5
x2 + 1 2x + 1 2 2
x(x2) 1+ x(x2) 1+ x + (x2)
1 5
1 2x + 2(x2)
Solutionbank
Edexcel AS and A Level Modular Mathematics
Partial fractions
Exercise F, Question 2
Question:
3x + 1
(a)
x2 + 2x + 1
2x2 + 2x 8
(b)
x2 + 2x 3
3x2 + 12x + 8
(c)
(x+2) 3
x4
(d)
x2 2x + 1
Solution:
3x + 1 3x + 1
(a) Repeated factor in denominator
x2 + 2x + 1 (x+1) 2
3x + 1 A B A(x+1) +B
Let 2
(x+1) + 2
(x+1) (x+1) (x+1) 2
Set the numerators equal: 3x + 1 A ( x + 1 ) + B
Substitute x = 1 3 + 1 = A 0 + B
B= 2
Equate coefficients of x: 3=A
A=3
3x + 1 3x + 1 3 2
Hence (x+1)
x2 + 2x + 1 (x+1) 2 (x+1) 2
2x2 + 2x 8
(b) is an improper fraction
x2 + 2x 3
Dividing gives
2x2 + 2x 8 2x 2
Therefore 2+ Factorise the denominator
x2 + 2x 3 x2 + 2x 3
2x 2
2+ (x+3) (x1)
2x 2 A B A(x1) +B(x+3)
Let (x+3) (x1) (x+3) + (x1) (x+3) (x1)
Set the numerators equal: 2x 2 A ( x 1 ) + B ( x + 3 )
Substitute x = 1 2 2 = A 0 + B 4
4 = 4B
B= 1
Substitute x = 3 62=A ( 4) +B0
4 = 4A
A= 1
Hence
2x2 + 2x 8 2x 2
2+
x2 + 2x 3 (x+3) (x1)
1 1
2 (x+3) (x1)
3x2 + 12x + 8 A B C
(c) Let 3 (x+2) + +
(x+2) (x+2) 2 (x+2) 3
A(x+2) 2+B(x+2) +C
(x+2) 3
Set the numerators equal:
3x2 + 12x + 8 A ( x + 2 ) 2 + B ( x + 2 ) + C
Substitute x = 2 12 24 + 8 = A 0 + B 0 + C
C= 4
Equate coefficients in x2: 3=A
A=3
Equate coefficients in x: 12 = 4A + B Substitute A = 3
12 = 12 + B
B=0
3x2 + 12x + 8 3 4
Hence 3 (x+2)
(x+2) (x+2) 3
x4 x4 + 0x3 + 0x2 + 0x + 0
(d)
x2 2x + 1 x2 2x + 1
Divide the numerator by the denominator:
Therefore
x4 4x 3
x2 + 2x + 3 + Factorise the denominator
x2 2x + 1 x2 2x + 1
4x 3
x2 + 2x + 3 +
(x1) 2
4x 3 A B A(x1) +B
Let 2
(x1) + 2
(x1) (x1) (x1) 2
Set the numerators equal: 4x 3 A ( x 1 ) + B
Substitute x = 1 4 3 = B B = 1
Equate coefficients in x: 4=A
Hence
x4 4x 3 4 1
x2 + 2x + 3 + x2 + 2x + 3 + +
x2 2x + 1 (x1) 2 (x1) (x1) 2
Solutionbank
Edexcel AS and A Level Modular Mathematics
Partial fractions
Exercise F, Question 3
Question:
Solution:
(a) f ( 3 ) = 2 ( 27 ) + 9 9 + 10 ( 3 )
+ 3 = 54 + 81 30 + 3 = 0
Therefore 3 is a root ( x + 3 ) is a factor
10 = 1.25B
B=8
10 1 8 5
Hence f(x) (x+3) + ( 2x + 1 ) (x+1)